2007
DOI: 10.1002/app.27050
|View full text |Cite
|
Sign up to set email alerts
|

Particle growth behavior of poly(methyl methacrylate) nanoparticles synthesized by the reversible addition fragmentation transfer living radical polymerization reaction

Abstract: PMMA nanoparticles with highly mono-dispersed size distribution were prepared using the RAFT living radical emulsion polymerization technique. A novel suriniferter for the RAFT reaction, DTBA, was synthesized and its chemical structure was identified using several spectroscopic techniques. The relationship between the particle size and the molecular weight of the polymer was investigated measuring the rate of growth of each during formation of particles, and was well explained by the simple random flight molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Using this concept, Kwak et al 29 described for the first time the synthesis of monofunctional carboxylated poly(methyl methacrylate) using a surface-active iniferter, 4-diethylthiocarbamoylsulfanylmethylbenzoic acid. Kim employed the same molecule for the emulsion polymerization of styrene, 30 of methyl methacrylate 31 and the formation of core-shell particles. The reactive surfactant has the advantage of being covalently bound to the polymer chain, which is beneficial for most of the applications, as it reduces migration.…”
Section: Introductionmentioning
confidence: 99%
“…Using this concept, Kwak et al 29 described for the first time the synthesis of monofunctional carboxylated poly(methyl methacrylate) using a surface-active iniferter, 4-diethylthiocarbamoylsulfanylmethylbenzoic acid. Kim employed the same molecule for the emulsion polymerization of styrene, 30 of methyl methacrylate 31 and the formation of core-shell particles. The reactive surfactant has the advantage of being covalently bound to the polymer chain, which is beneficial for most of the applications, as it reduces migration.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of well‐defined star polymers with several arms via the ATRP approach have been reported in a number of papers 23–28. In particular, in recent years many reports have demonstrated that CRP can be applied to emulsion systems,29 which afford a ready access to obtain polymer particles with controlled compositions, architectures and functionalities 30–32. As a representative example of CRP, ATRP can be conducted in emulsion systems when the appropriate surfactant and ligand are employed 33–38.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled radical polymerization (CRP) processes have been proven to be versatile for the synthesis of polymers with well‐defined structures and complex architectures. In recent years, many reports have demonstrated that CRP is able to be applied to emulsion systems,40 which afford a facile access to obtain polymer particles with controlled compositions, architectures and functionalities 41–43. As a representative example of CRP, ATRP can be conducted in emulsion systems, when the appropriate surfactant and ligand are used 44–49…”
Section: Introductionmentioning
confidence: 99%